2020
DOI: 10.1038/s41598-020-59379-4
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing in Individuals with Isolated Biliary Atresia

Abstract: Biliary atresia (BA) is a severe pediatric liver disease resulting in necroinflammatory obliteration of the extrahepatic biliary tree. BA presents within the first few months of life as either an isolated finding or with additional syndromic features. The etiology of isolated BA is unknown, with evidence for infectious, environmental, and genetic risk factors described. However, to date, there are no definitive causal genes identified for isolated BA in humans, and the question of whether single gene defects p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…These studies showed that EHC and IHC depend on distinct arms of the glutathione metabolism pathway to maintain redox homeostasis. Our work further revealed that protein quality control (PQC) mechanisms work in concert with redox responses following biliatresone exposure, and genetic disruption of the heat shock chaperone 90 (HSP90) pathway genes (STIP1, REV1), implicated in human BA via whole exome sequencing, 11 altered biliatresone toxicity in the zebrafish and human cholangiocytes. Finally, we identified pharmacological activators of cGMP signaling as a class of drugs that work synergistically with NAC in attenuating biliatresone-mediated injury by enhancing PQC.…”
Section: Short Summarymentioning
confidence: 79%
See 1 more Smart Citation
“…These studies showed that EHC and IHC depend on distinct arms of the glutathione metabolism pathway to maintain redox homeostasis. Our work further revealed that protein quality control (PQC) mechanisms work in concert with redox responses following biliatresone exposure, and genetic disruption of the heat shock chaperone 90 (HSP90) pathway genes (STIP1, REV1), implicated in human BA via whole exome sequencing, 11 altered biliatresone toxicity in the zebrafish and human cholangiocytes. Finally, we identified pharmacological activators of cGMP signaling as a class of drugs that work synergistically with NAC in attenuating biliatresone-mediated injury by enhancing PQC.…”
Section: Short Summarymentioning
confidence: 79%
“…Whole exome sequencing recently identified potentially deleterious heterozygous variants in genes encoding HSP90 interactors STIP1 and REV1 in two individuals with isolated BA. 11 STIP1 is an evolutionarily conserved co-chaperone of HSP90 and HSP70. 22 REV1 is HSP90 client protein and functions as a Y-family polymerase that plays a central role in translesion DNA synthesis during replication stress.…”
Section: Validation Of Genetic Variants Linked To Hsp90 As Candidate Ba Risk Factorsmentioning
confidence: 99%
“…Intriguingly, inactivation of INVS in mouse model shows a signi cant increase in bilirubin level compared to that of the wild-type, and the pathogenic changes in ductal plate malformation in the intrahepatic biliary of the mutant mouse 51 . However, since then the association of INVS with BA had not been rmly established due to an absence of INVS mutations in patients with BA 52,53 . In fact, INVS mutations have been observed in patients with infantile nephronophthisis type 2 regardless of populations [54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…Rajagopalan et al . claimed that these mutations were due to exposure to toxic environmental factors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…STIP1 is a gene that helps the protein transfer response in heat shock response. Rajagopalan et al claimed that these mutations were due to exposure to toxic environ mental factors [25].…”
Section: Gene Number Of Snps Common To 10 Patientsmentioning
confidence: 99%